Pengaruh Financial Technology (Fintech) Terhadap Profitabilitas Perbankan - Khoirotun Niswa; Abdul Basyith (Jurnal Bisnis, Manajemen, dan Ekonomi, 2026)
Financial Technology is a combination of technology and financial systems. The aim of this research is to determine the influence of financial technology on banking profitability. Financial Technology is measured by the number of ATM users, Mobile Banking, and Internet Banking. Meanwhile, profitability is measured by Return On Asset (ROA), Return On Equity (ROE), and Net Interest Margin (NIM). The samples in this study were BRI Bank, Mandiri Bank, BNI Bank, BTN Bank, BCA Bank, CIMB Niaga Bank, Permata Bank, and OCBC NISP Bank, which were listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 Period. The sampling method used was purposive sampling, with multiple regression analysis. The analysis of ROA indicates that ATM has a significant effect on ROA. Mobile Banking has a significant positive effect on ROA, and Internet Banking has a significant effect on ROA. The results of the ROE analysis indicate that ATM has a significant effect on ROE. Mobile Banking has a significant effect on ROE, and Internet Banking has a significant positive effect on ROE. The analysis of NIM indicates that ATM has a significant effect on NIM. Mobile Banking has a significant positive effect on NIM, and Internet Banking has a significant effect on NIM.